Accounting for spectral shape in a simplified method of analyzing friction pendulum systems. (1st November 2020) - Yang, Tianye; Marafi, Nasser A.; Calvi, Paolo M.; Wiebe, Richard; Eberhard, Marc O.; Berman, Jeffrey W.
Highlights: Subduction zone with basin amplification modifies characteristics of ground motions. Simplified methods of analyzing friction pendulum systems do not always produce accurate results. Displacement-spectrum shape correction factor is proposed. Abstract: This paper examines the effect of subduction zone and basin amplified motions on the accuracy of using a simplified method to analyze Friction Pendulum Systems, which is the basis for many international code provisions. This method estimates the maximum displacement demand for Friction Pendulum System isolated structures from analyzing a single degree of freedom system with equivalent period and damping coefficient. Friction Pendulum Systems with equivalent natural period between 1.5 s and 5 s and equivalent damping ratio from 16% to 32% were considered when subjected to over 400 motions. The considered ground motions include crustal and subduction zone motions, with and without basin amplification effect. Ratios of analysis-to-design maximum displacements corresponding to each ground motion are computed. A displacement-spectrum shape correction factor is proposed to improve the accuracy of the simplified method. This correction factor takes into account the irregularity of the 5% damped displacement spectrum that depends on the equivalent period and damping ratio at design displacement of the isolation system.